DOI: 10.26481/dis.19930101jm
|View full text |Cite
|
Sign up to set email alerts
|

De rol van tutoren in probleemgestuurd onderwijs : contrasten tussen student- en docent-tutoren

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…During the course evaluation at the end of the course, students reported their average self-study time for group meetings in hours. A study by Moust (1993) indicated that this method of self-reported study time is an accurate reflection of the actual time spent on self-study.…”
Section: Methodsmentioning
confidence: 99%
“…During the course evaluation at the end of the course, students reported their average self-study time for group meetings in hours. A study by Moust (1993) indicated that this method of self-reported study time is an accurate reflection of the actual time spent on self-study.…”
Section: Methodsmentioning
confidence: 99%